El Profesor de religión (Journal of Parents and Teachers, 2014)
The article discusses the nature of the profession of the teacher of religion. Thus, the author presents some assumptions and a wide range of tasks of the teaching profession. Finally, the most important thematic blocks of the religion class are included.
Keywords: Religion; Education; Teacher; Charisma